2019
DOI: 10.2116/analsci.19n018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nitrogen-containing Compounds in Mouth-exhaled Breath by Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry

Abstract: Nitrogen-containing compounds are important components in human breath. However, their origins have not yet been clearly understood. In this study, a modified electrospray ionization (ESI) source coupling with quadrupole time-of-flight mass spectrometry has been used for breath analysis. Fourteen nitrogen-containing compounds were identified in mouthexhaled breath, and 10 of them were from the oral cavity and oropharynx. Moreover, 8 of these nitrogen-containing compounds were recognized as endogenous metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Despite being detected in human exhaled breath studies, its atmospheric pathway remains unclear. 43 In our study, we observed a significant difference in concentrations between autumn and winter, with higher levels observed during autumn and notably lower levels observed during winter (Text S5). ε-Caprolactam may contribute to PM 2.5 through industrial emissions, atmospheric chemical reactions, and potential adherence of metabolites to existing particles.…”
Section: Chon Compoundssupporting
confidence: 46%
See 1 more Smart Citation
“…Despite being detected in human exhaled breath studies, its atmospheric pathway remains unclear. 43 In our study, we observed a significant difference in concentrations between autumn and winter, with higher levels observed during autumn and notably lower levels observed during winter (Text S5). ε-Caprolactam may contribute to PM 2.5 through industrial emissions, atmospheric chemical reactions, and potential adherence of metabolites to existing particles.…”
Section: Chon Compoundssupporting
confidence: 46%
“…ε-Caprolactam is commonly used in synthetic fiber manufacturing and various other industrial processes. Despite being detected in human exhaled breath studies, its atmospheric pathway remains unclear . In our study, we observed a significant difference in concentrations between autumn and winter, with higher levels observed during autumn and notably lower levels observed during winter (Text S5).…”
Section: Resultsmentioning
confidence: 61%